2007
DOI: 10.1162/pres.16.4.385
|View full text |Cite
|
Sign up to set email alerts
|

Motion Compression for Telepresence Locomotion

Abstract: A telepresence system enables a user in a local environment to maneuver in a remote or virtual space through a robotic operator (agent). In order to ensure a high degree of telepresence realism, it is critical that the local user has the ability to control the remote agent's movement through the user's own locomotion. The required motion of the remote agent is determined according to its environment and the specific task it is to perform. The local user's environment is usually different from that of the remot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…In the past, prediction for redirected walking was done by estimating a single future path which was then transformed to keep the user inside the tracking space [5,16,22,24]. These predictions were made based on the user's current viewing direction, direction of movement, past movement or a combination thereof.…”
Section: Prediction For Redirected Walkingmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, prediction for redirected walking was done by estimating a single future path which was then transformed to keep the user inside the tracking space [5,16,22,24]. These predictions were made based on the user's current viewing direction, direction of movement, past movement or a combination thereof.…”
Section: Prediction For Redirected Walkingmentioning
confidence: 99%
“…These predictions were made based on the user's current viewing direction, direction of movement, past movement or a combination thereof. The resulting prediction is a single straight line path with the exception of Su et al [24] who fitted a curved path based on the user's past path. However, a model predictive control planner for redirected walking can consider multiple branching paths in its planning process, and to take full advantage of its potential we require a prediction that provides multiple future paths together with their respective probability.…”
Section: Prediction For Redirected Walkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Engel et al [3] proposed a psychophysically calibrated controller that employs a cost function based on the noticeability of redirection. Nitzsche et al [12] and Su et al [19] suggested an approach that dynamically minimizes the introduced curvature, but does not make imperceptibility a primary goal. A new way for planning RETs was proposed by Zmuda et al [25].…”
Section: Related Workmentioning
confidence: 99%
“…Another approach for the user's future path was introduced by [11]. Here, the future walking direction is simply determined by a linear extrapolation of the user's previous path.…”
Section: Introductionmentioning
confidence: 99%